Talking about health: Community ambassadors as a health promotion strategy to increase breast and bowel cancer screening in regional Australia. Issue 1 (18th July 2022) - James, Alexandra; Chamberlain, Daniel; Azar, Denise; Sewell, Lauren
Abstract: Issue addressed: In Australia, cancer is the leading contributor to disease burden, with breast and bowel cancer among the most commonly diagnosed cancers. Despite the presence of community‐wide health promotion activities and screening programs, people living in regional and rural locations experience a number of factors that reduce breast and bowel cancer survival outcomes. This study investigates the ways that high‐risk community members in a regional area of Australia interact with health messaging about breast and bowel cancer screening. Methods: A qualitative research method was used to conduct 31 in‐depth one‐on‐one interviews with community members, leaders and essential service providers. A thematic approach was used to analyse data. Results: Findings provided insight to the ways that health is spoken about within the community, what prompts discussion of health, trustworthy sources of health information and the significance of peer‐to‐peer communication. Conclusions: Existing community communication lines can be used to assist in delivering public health messages among high‐risk and vulnerable population groups. Utilising community ambassadors is identified as a health promotion method for hard‐to‐reach populations. So What?: Conversations about health and screening amongst community members, and led by community members, play a key role in shaping engagement with cancer screening programs and represent an important site for health promotion activities. These findings have implications for future public health initiatives amongst high‐risk groups in regional locations.